Bicultural Identity Integration (BII): Components, psychosocial antecedents, and outcomes - BENET-MARTINEZ, Verónica (Institutional Knowledge at Singapore Management University, 2021)
In Western societies, the number of racial, ethnic, and cultural minorities is clearly increasing. Not surprisingly, discussions about the consequences of cultural diversity and how to best manage its potential consequences, both negative (e.g., ethnic conflict, lowering of social trust, identity confusion) and positive (e.g., increased productivity, development of multicultural and multilingual competencies), have become a regular feature of academic, public, and political debates. This chapter reviews and integrates relevant findings and theories on the construct of bicultural identity integration (BII) and proposes an agenda for future studies. Toward that goal, it includes sections not only describing the nature of BII and its antecedents and development, but also its measurement, its social and cognitive consequences, and its relevance to social constructs beyond ethnicity and culture. Because biculturalism and multiculturalism issues are still relatively new to mainstream social and personality psychology, the chapter starts with an introductory section devoted to defining the constructs of multiculturalism and multicultural identity (at the individual, social, and intergroup levels) and to discussing key issues from the relevant fields of acculturation, social-personality and cultural psychologies, and interculturalism studies.